ANALISIS PRIORITAS MASALAH KESEHATAN MASYARAKAT DESA TANJUNG LAIMEO DENGAN METODE CARL - Irma, Irma (Yayasan Nuraini Ibrahim Mandiri, 2026)
Health problems are one of the important elements in the development program of the nation and state. Public health status is influenced by four main factors, namely environmental factors, behavior/lifestyle, health services and genetics or heredity. Health problems that occur in Tanjung Laimeo Village, Sawah District, North Konawe Regency are caused by various factors. This study aims to determine priority health problems in Tanjung Laimeo Village. This study is a descriptive observational study with 55 respondents. This study was conducted in Laimeo Village, Sawah District, North Konawe Regency from January 29 to February 11, 2026. Data were collected through document searches at the community health center and direct interviews with respondents. Data analysis to determine priority health problems used the CARL method (Capability; Accessibility; Readiness; Leverage). Scoring is based on mutual agreement, namely 1 = Very not a problem; 2 = not a problem; 3 = quite a problem; 4 = Very much a problem; and 5 = Very much a problem (absolute). Furthermore, the results of the subsequent analysis are presented in tabular form and accompanied by a narrative.